2020
DOI: 10.1080/1750399x.2020.1839998
|View full text |Cite
|
Sign up to set email alerts
|

The ergonomics of translation tools: understanding when less is actually more

Abstract: Professional translation and consequently translation training involve a wide range of general-purpose technological aids as well as specifically-designed translation tools. In response to market demands, a great deal of effort has been devoted to developing and implementing features in such tools that can contribute to higher consistency, productivity and quality. There has been less attention paid to the needs of learners and actual users, however. Previous research with professional translators at the workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…In this way, students are also given an opportunity to select the tool that they find as the easiest and most comfortable to use in terms of the interface of the software. This was explained by Kappus & Ehrensberger-Dow (2020) within the scope of ergonomics of translation tools, in which they found that the more complicated a tool's interface is, the less optimal use it offers, which in turn makes the translators' workflow be interrupted and their cognitive load be increased.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, students are also given an opportunity to select the tool that they find as the easiest and most comfortable to use in terms of the interface of the software. This was explained by Kappus & Ehrensberger-Dow (2020) within the scope of ergonomics of translation tools, in which they found that the more complicated a tool's interface is, the less optimal use it offers, which in turn makes the translators' workflow be interrupted and their cognitive load be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Vroeger streefden CAT-toolontwikkelaars naar een zo groot mogelijk aanbod aan functionaliteiten. Tegenwoordig bieden ze die functionaliteiten nog wel aan, maar willen ze de vertaler de vrijheid geven om de omgeving te 'customizen' (Kappus & Ehrensberger-Dow 2020). Ze hanteren steeds vaker een 'opt-inconstructie', waarbij je moet aangeven welke functie je nuttig vindt en welke niet (Moorkens & O'Brien 2017).…”
Section: Nuttige Toolsunclassified
“…As long as the MT output is not so poor that the post-editor decides to translate everything from scratch, or not so good that the post-editor could accept unedited raw MT, it is safe to say that a PE process entails evaluation of MT output, correction of MT errors, and translation from scratch at different levels. The extraneous cognitive load in PE is caused by external factors such as the user interface and working environment where a PE task is performed, which is gaining increasing interest in usability and ergonomics research (Kappus & Ehrensberger-Dow, 2020).…”
Section: Causal Factors Of Pe Task Difficultymentioning
confidence: 99%